2008
DOI: 10.1016/j.mce.2008.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor expression during C2C12 skeletal muscle cell line differentiation

Abstract: SUMMARYThe Androgen Receptor (AR) pathway is involved in the development of skeletal muscle but the molecular basis of androgen-related myogenic enhancement are still unclear. We have investigated AR expression and localization during myoblasts-myotubes differentiation in skeletal muscle cell line C2C12. AR expression increases during proliferation and commitment phase and its levels remain elevated in myotubes. In proliferating and committed cells in the absence of testosterone, AR protein localizes in the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 46 publications
3
36
0
Order By: Relevance
“…The present study supports a role for testosterone in enhancing myogenic differentiation and myotube hypertrophy [50][51][52][53][54][55] but more importantly, shows the capacity to improve hypertrophy and myonuclear accretion in a previously established model displaying impaired differentiation and hypertrophy similar to that of atrophic phenotypes such as ageing [7,26]. Furthermore, testosterone treatment enhanced hypertrophy shown by increases in myotube diameter, nuclei per myotube and a larger number of myotubes with 5 or more nuclei in both control (CON) and multiple population doubling (PD) cells.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The present study supports a role for testosterone in enhancing myogenic differentiation and myotube hypertrophy [50][51][52][53][54][55] but more importantly, shows the capacity to improve hypertrophy and myonuclear accretion in a previously established model displaying impaired differentiation and hypertrophy similar to that of atrophic phenotypes such as ageing [7,26]. Furthermore, testosterone treatment enhanced hypertrophy shown by increases in myotube diameter, nuclei per myotube and a larger number of myotubes with 5 or more nuclei in both control (CON) and multiple population doubling (PD) cells.…”
Section: Discussionsupporting
confidence: 86%
“…Testosterone has previously been shown to increase myogenin in C2C12 cells [50,51]. Indeed, community-dwelling older men treated with grades doses of testosterone show increases in muscle fibre size accompanied by increased myogenin expression [55].…”
Section: Discussionmentioning
confidence: 97%
“…In a study done on stromal cells, estradiol reduced the expression of both AR and ER (Smith et al 2002), in line with our finding on the AR mRNA expression, but differs with the ER mRNA expression data, which was not altered after sex hormone treatment or between sexes. In addition, AR expression was increased after chronic testosterone treatment in a C2C12 skeletal muscle cell line and during differentiation (Wannenes et al 2008), and this effect was also observed in mesenchymal, pluripotent cell line after exposure to testosterone (Singh et al 2003). However, our finding may indicate a negative feedback loop of chronic testosterone exposure on its own receptor in human myotubes.…”
Section: Discussionsupporting
confidence: 55%
“…Dio is a component of the steroid sapogenin and was previously detected in the plasma of rats and humans after oral administration (15,16), showing that the orally taken Dio may be adsorbed and act directly on the tissues in the body. Meanwhile, in previous studies, Dio increased serum dehydroepiandrosterone (DHEA) levels (20) and DHEA is believed to act as a precursor of testosterone, that induces skeletal muscle differentiation (21)(22)(23). Thus, the adsorbed Dio may also act indirectly on skeletal muscles, leading to increased the numbers of muscle fibers.…”
Section: Dio Blocks Chronic High Chol Diet-induced Lipid Accumulationmentioning
confidence: 97%